Calibration of the Dutch‐Flemish PROMIS Pain Behavior item bank in patients with chronic pain. (26th May 2015) - Crins, M.H.P.; Roorda, L.D.; Smits, N.; de Vet, H.C.W.; Westhovens, R.; Cella, D.; Cook, K.F.; Revicki, D.; van Leeuwen, J.; Boers, M.; Dekker, J.; Terwee, C.B.
Abstract: Background: The aims of the current study were to calibrate the item parameters of the Dutch‐Flemish PROMIS Pain Behavior item bank using a sample of Dutch patients with chronic pain and to evaluate cross‐cultural validity between the Dutch‐Flemish and the US PROMIS Pain Behavior item banks. Furthermore, reliability and construct validity of the Dutch‐Flemish PROMIS Pain Behavior item bank were evaluated. Methods: The 39 items in the bank were completed by 1042 Dutch patients with chronic pain. To evaluate unidimensionality, a one‐factor confirmatory factor analysis (CFA) was performed. A graded response model (GRM) was used to calibrate the items. To evaluate cross‐cultural validity, Differential item functioning (DIF) for language (Dutch vs. English) was evaluated. Reliability of the item bank was also examined and construct validity was studied using several legacy instruments, e.g. the Roland Morris Disability Questionnaire. Results: CFA supported the unidimensionality of the Dutch‐Flemish PROMIS Pain Behavior item bank (CFI = 0.960, TLI = 0.958), the data also fit the GRM, and demonstrated good coverage across the pain behavior construct (threshold parameters range: −3.42 to 3.54). Analysis showed good cross‐cultural validity (only six DIF items), reliability (Cronbach's α = 0.95) and construct validity (all correlations ≥0.53). Conclusions: The Dutch‐Flemish PROMIS Pain Behavior item bank was found to have good cross‐cultural validity, reliability and construct validity. The development of the Dutch‐Flemish PROMIS Pain Behavior item bank will serve as the basis for Dutch‐Flemish PROMIS short forms and computer adaptive testing (CAT).